Studi Kinerja Struktur Beton Bertulang Beraturan Yang Didisain Dengan Performance Based Plastic Design - Nidiasari, Nidiasari; Sunaryati, Jati; Finanda, Sandy (Jurnal Bangunan, Konstruksi & Desain, 2023)
Indonesia is a country that has a very high level of seismicity. It is necessary to plan a building structure that can withstand the earthquake load. Indonesia has adopted guidelines on earthquake resistance planning procedures for buildings and non-buildings. This guideline uses the Performance-Based Seismic Design (PBSD) concept. Performance-Based Plastic Design (PBPD) is a structural analysis with the concept of energy methods which was initially used on steel structures. For reinforced concrete structures this method can also be used using the C2 coefficient. To determine the performance level of structures designed using the Performance-Based Plastic Design method, an analysis of the five-story reinforced concrete structure was carried out. Next, the structure will be analyzed using pushover loads. From the structural performance analysis, the structural ductility value based on Performance-Based Plastic Design (PBPD) was 3.014. The performance level is based on the capacity spectrum at the immediate occupancy level.